Maximum principle for the Laplacian with respect to the measure in a domain of the Hilbert space - Bogdanskii, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We obtain the maximum principle for two versions of the Laplacian with respect to the measure, namely, for the “classical” and “L^2” versions in a domain of the Hilbert space.